Análisis de las demandas físicas durante los movimientos de ataque finalizados en bandejas, tiros de dos puntos y tres puntos - Calderani Junior, A.; Ribeiro, R. A.; Shoiti Misuta, M.; Allegretti Mercadante, L. (Revista Ciencia del Deporte, 2020)
The main aim of this study was describing physical demands variables at 5-man offense and fast-breaks finished in successful and unsuccessful shooting movements in basketball games. Physical (velocity and distance covered) and technical (two-point, three-point shoot and layups) parameters were quantified. The attacks were separated in 5-man offense and fast-breaks. For identification of 5-man offense beginning, was utilized criterions based on the positional information of players on court. The fast-breaks were considered all attacks that were not identified by the 5-man offense criteria. All velocity and distance covered data from offensive player were summed up in each attack, producing team`s velocity and distance covered. Distance covered in 5-man offense with unsuccessful layups were significantly lower than the successful ones. In the comparison between 5-man offense and fast-breaks finished in two-point shots, both variables of the offensive teams were significantly higher for fast-breaks. Greater means also were observed at the distance covered and velocity for the fast-breaks finished with layups. Players need to perform higher distances in their offensive displacements for a better performance in layups actions. Given the greater variability of velocity observed in fast-break situations, a better physical conditioning, aimed specifically to player with constantly participations in these situations, with focus on the variability of its intensity is needed.